Peran Design Thinking dalam Meningkatkan Kepribadian Kreatif dan Etis melalui Soft Skill serta Branding Digital - Diana Zumrotus Sa’adah; Egi Sri Lestari; Anindya Cahya Putri; Elvina Triya Rahmahnusiya; Muhammad Yusuf Mahmudi; Sulthan Muhammad Alfaris (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The development of digital technology has transformed the way humans think, interact, and solve problems in various aspects of life. In this context, design thinking emerges as a creative, empathetic, and innovative mindset centered on human needs to address complex challenges in the digital era. This study aims to analyze the role of design thinking in fostering creative and ethical personalities through the strengthening of soft skills and social media branding and analyze the role of design thinking in developing creative and ethical personalities through strengthening soft skills and social media branding in the digital era. Using a descriptive qualitative approach, this research will explore how the application of design thinking can encourage individuals to think innovatively and responsibly, as well as how social media branding can strengthen self-image and digital ethical values. The research employs a qualitative descriptive approach using literature review methods based on relevant national and international sources. The study's findings indicate that design thinking plays a crucial role in fostering innovative mindsets, empathy, and moral responsibility, which form the foundation for developing a creative personality. Meanwhile, social media branding serves as a means to strengthen self-image, digital ethical values, and personal integrity online.